"Development of a Real-Time Adherence to Mine Plan Tools as Part of an Integrated Remote Mine Control Centre" - S D. Dessureault (The Australasian Institute of Mining and Metallurgy, 2011)
In one of North AmericaÆs largest mines, which contains more than six active coal-producing faces, mine controllers must meet the complex challenge of adhering to the mine plan while also ensuring customer quality. Fleet management systems (FMS) provide many different avenues to control production flows, from the faces to the various pit crushers. Nonetheless, mine controllers must balance a variety of factors such as unplanned downs, differing customer demands, their own daily key performance indicators (KPIs) related to equipment utilisation, among others. Deviating from the short-term mine plan is the most common means of balancing the other factors, since adherence to the plan is traditionally only measured during the weekly variance meeting with engineering staff. However, such deviation may be one of the most costly responses, as long-term scheduling issues may arise such as multi-face dead-heading or insufficient stripping. This paper focuses on the development of a system for real-time adherence to mine plan within a control room environment. This system is part of a larger blending-focused, multi-million dollar project with elements of a centralised remote control room, developed at the University of ArizonaÆs Mining Information Systems and Operations Management (MISOM) Mine Control Center (MC2). The mine plan (MPL) component of the overall blending system integrates both historical and real-time FMS data with mine plan requirements directly sourced from original systems (no additional input required). The measures, displayed largely as graphs, have tools to help controllers manage the production to facilitate adherence to the plan. Some measures are designed to motivate crews to perform by inciting competition between crews, softened through a study of the controller culture. The MPL component was deployed at the mine, and the before and after deployment adherence was measured. This paper discusses the technical development of the new tool, its deployment, and an ethnography (study of culture) to understand controller motivation.